1995
DOI: 10.1111/j.1476-5381.1995.tb15111.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase in human placenta and umbilical cord from normal, intrauterine growth‐retarded and pre‐eclamptic pregnancies

Abstract: 1 It has been suggested that a deficiency of nitric oxide (NO) may explain many of the pathophysiological features of pre-eclampsia (PE) and intra-uterine (foetal) growth retardation (IUGR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 68 publications
4
34
0
Order By: Relevance
“…This observation suggests that elevated maternal ADMA (raised in DDAH1 (wt/del) heterozygotes (Leiper et al, 2007)) may negatively impact embryonic viability post-implantation. Consistent with this suggestion, elevated plasma ADMA levels have been reported in human pre-eclampsia (Savvidou et al, 2003) and intrauterine growth retardation (Rutherford et al, 1995). …”
Section: Discussionsupporting
confidence: 69%
“…This observation suggests that elevated maternal ADMA (raised in DDAH1 (wt/del) heterozygotes (Leiper et al, 2007)) may negatively impact embryonic viability post-implantation. Consistent with this suggestion, elevated plasma ADMA levels have been reported in human pre-eclampsia (Savvidou et al, 2003) and intrauterine growth retardation (Rutherford et al, 1995). …”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have reported reduction in NOS activity in the umbilical artery endothelium, 27 and fetoplacental NO synthesis is decreased during pregnancies complicated by fetal growth restriction. 28,29 On the other hand, other authors have found that concentrations of plasma nitrates and nitrites are higher in the fetal circulation of growth-restriction pregnancies in comparison with normal pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, women with intrauterine growth-restricted pregnancies have a lower NO-dependent flow-mediated dilation and a higher plasma level of asymmetric dimethylarginine (ADMA), an inhibitor of eNOS that competes with L-arginine, than women with normal pregnancies. 15 In addition, a lower eNOS expression in the umbilical artery 16 and a lower eNOS activity in placental villus tissue 17 are found in intrauterine growthrestricted compared with normal pregnancies. In an earlier study, we found a smaller fetal outcome and lower eNOS activity and concentration in fetal umbilical veins exposed to maternal smoking compared with those of lifelong nonsmoking mothers.…”
Section: Clinical Perspective P 864mentioning
confidence: 99%